Wanita dan Amalan Penyusuan Bayi Di Perupok, Bachok, Kelantan (Jurnal Pembangunan Sosial, 2009)
The health of an infant is determined by numerous factors related to woman directly and indirectly. The best infant food is derived from the mother. By giving the infant colostrums and breast milk is a good beginning for the health of an infant. Infants fed on motherâ€™s milk have better chance of survival than those fed on other types of milk. The paper discusses women and colostrums, factors affecting the choice of infant food and women views on solid food and the practice ofâ€™â€œcerai susuâ€. The paper argues that the socio-cultural and economic consideration play the deterring factor in infant feeding practices. Discussion here is based on observation and interview with 30 women informants and several key informants in Perupok, Bachok, Kelantan from 2002 to 2004. The important finding is the women do not know about colostrums and considered it as dirty, not milk and harmful to babies. Majority women who breast feed only or breast feed for a short period are not working in formal sector, with few children and do not have a reasonable household income. While women who bottle feed only, are young and with only one child or HIVpositive mothers. For the latter, the health authority advises them not to do so. The study also identified socio-cultural and economic factors influencing women decision on the type of feeding for their babies